The Analysis Strategy of Coastal Women Empowerment in Lambangi Village Kolono East District South Konawe Regency - Hartina Batoa; Yoenita Jayadisastra; Sukmawati Abdullah; Idrus Salam; Megawafirmawanti Lasinta; Nur Adzy (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2022)
This study aims to analyse the process of empowering coastal women in Lambangi Village, identifying internal and external factors to formulate and determine priority strategies for empowering coastal communities. This study collected data through observation, interviews, documentation studies, simple quantitative data analysis with class intervals, and SWOT analysis. The results showed that the average percentage of empowering coastal women through the coco pot business in Lambangi Village was 87.36%, consisting of preparation, assessment, planning, formalisation of action plans, implementation, evaluation and termination. The strategy that must be implemented consists of increasing human resources, intensifying the use of social media for online marketing, and collaborating with the government to participate in exhibitions as a venue for expanding offline marketing networks.